The Thoughts and Views of Ja’far Mahmud Adam on Marriage, Family Institution and Women Issues - Ismail Hashim Abubakar (Fakultas Syariah IAIN Madura, 2023)
Marriage is the foundation upon which a family institution is erected and it is one of cogent measures that Islam enjoins in preserving public morality and developing a healthy and sane society. Furthermore, there is virtually a consensus among all cultures that marriage has been over the centuries the most legally acceptable gateway and conventional source of establishing a family institution. Henceforth, marriage assumes a special significance and occupies a pivotal place owing to its crucial role in building a society and ensuring the continuity of human survival. Meanwhile, albeit there are universally shared codes and conventionally accepted norms and values, geographical space, cultures, civilizations and religious orientations have a great stake in determining ways and lifestyles of people vis-à-vis ways the continuity of human survival is sustained. Marriage and its associated components like the phenomenon of woman represent areas that expose the extent of clash of civilizations. Guided by their religious precepts and legal provisions, Muslim scholars and thinkers tend to situate Islam as the most moderate ideological culture that formulates the most universally suitable and pragmatic systems which deal with marriage, growing a family and general treatment of women.